2012
DOI: 10.1126/science.1220834
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Fusions of FGFR and TACC Genes in Human Glioblastoma

Abstract: Oncogenic TACC-tics Human cancers exhibit many types of genomic rearrangements—including some that juxtapose sequences from two unrelated genes—thereby creating fusion proteins with oncogenic activity. Functional analysis of these fusion genes can provide mechanistic insights into tumorigenesis and potentially lead to effective drugs, as famously illustrated by the BCR-ABL gene in chronic myelogenous leukemia. Singh et al. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
642
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 677 publications
(720 citation statements)
references
References 28 publications
40
642
1
2
Order By: Relevance
“…However, previous studies have found the FGFR3-TACC3 fusion protein localized only to the mitotic spindle poles during mitosis, and relocated during late stage mitosis to the midbody. A mechanism for this change in recruitment and the role of FGFR3-TACC3 during interphase remains unclear (46).…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have found the FGFR3-TACC3 fusion protein localized only to the mitotic spindle poles during mitosis, and relocated during late stage mitosis to the midbody. A mechanism for this change in recruitment and the role of FGFR3-TACC3 during interphase remains unclear (46).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of FGFR-dependent signaling pathways can stimulate tumor initiation, progression, and resistance to therapy. Translocation events implicating the FGFR1 gene and various fusions of FGFR1 are found in myeloproliferative syndromes (12); chromosomal translocations of FGFR1 or FGFR3 and the transforming acidic coiled-coil genes (TACC1 or TACC3) are oncogenic in glioblastoma multiforme, bladder cancer, head and neck cancer, and lung cancer (13)(14)(15)(16); oncogenic mutations of FGFR2 and FGFR3 are observed in lung squamous cell carcinoma; FGFR2 N549K is observed in 25% of endometrial cancers; FGFR3 t(4;14) alterations are reported in 15-20% of multiple myeloma (17)(18)(19); FGFR4 Y367C mutation in the transmembrane domain drives constitutive activation and enhanced tumorigenic phenotypes in a breast carcinoma cell line (20)(21)(22); and K535 and E550 mutants are reported to activate FGFR4 in rhabdomyosarcoma (23). FGFR amplification is reported in various cancers (24,25): FGFR1 is amplified in colorectal, lung, and renal cell cancers (26,27); FGFR2 is amplified in gastric cancer and colorectal cancer (28,29); FGFR3 is commonly amplified in bladder cancer and also is reported for cervical, oral, and hematological cancers (30)(31)(32); and FGFR4 is amplified in hepatocellular carcinoma, gastric cancer, pancreatic cancer, and ovarian cancer (33)(34)(35)(36)(37).…”
Section: Significancementioning
confidence: 99%
“…In addition, this fusion protein serves as a therapeutic target for the successful drug imatinib (4). In solid human tumors, fusion genes such as the TMPRSS2-ERG fusion in prostate cancer (5), FGFR-TACC in glioblastoma (6), and DNAJB1-PRKACA in liver cancer (7) are important molecular signatures for understanding cancer mechanisms and stratifying patient groups.…”
mentioning
confidence: 99%